2013
DOI: 10.2514/1.i010080
|View full text |Cite|
|
Sign up to set email alerts
|

Discovering Anomalous Aviation Safety Events Using Scalable Data Mining Algorithms

Abstract: The worldwide civilian aviation system is one of the most complex dynamical systems ever created. Most modern commercial aircraft have onboard flight data recorders (FDR) that record several hundred discrete and continuous parameters at approximately 1 Hz for the entire duration of the flight. This data contains information about the flight control systems, actuators, engines, landing gear, avionics, and pilot commands. In this paper we discuss recent advances in the development of a novel knowledge discovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Moreover, how to characterize the temporal structure during various flight phases remains unresolved. Most recently, Matthews et al summarize the knowledge discovery pipeline for aviation data using these algorithms discussed above [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, how to characterize the temporal structure during various flight phases remains unresolved. Most recently, Matthews et al summarize the knowledge discovery pipeline for aviation data using these algorithms discussed above [10].…”
Section: Introductionmentioning
confidence: 99%
“…It could be shown that in conjunction with expert knowledge these approaches did produce meaningful results, some of them clearly safety-relevant. Matthews et al (2013) investigated the use of different data mining algorithms to identify safety-relevant occurrences of different varieties in up to 19,243 flights. They found that in collaboration with review pilots it was possible to detect novel threats through this data mining approach.…”
Section: Machine Learning In Flight Data Monitoringmentioning
confidence: 99%
“…One-class SVM [39] is then used to construct a separating hyperplane to detect anomalies. This method was applied to the FOQA dataset [33] and showed high accuracy in discovering operationally significant aviation safety events.…”
Section: Related Workmentioning
confidence: 99%